Investigating the Philosophical Basis of "Design" as a Technological Activity, considering the implicit meanings in the intertextual concept of "Techne" - Seyyed Ali Faregh; Yasaman Hajian Foroushani (Journal of Philosophical Investigations, 2022)
According to "Design" theorists, ambiguity in essence and meaning has posed various challenges to this scientific field, and since a lack of understanding of the functions and philosophical foundations of a scientific field makes it impossible to realize the appropriate or complete version of that field, design researchers have focused on expanding their understanding of the field mentioned above. This descriptive-analytical study focuses on the theoretical field of "design philosophy" and will be valuable for furthering the discussion on design's essence. Concerning this, this research will address the following questions: "What are the philosophical underpinnings of the act of design as a technological action?" and "How can the act of design be discussed in terms of the various implications of the notion of Techne?". To answer these questions, we will first examine the discussions over the concept of "design" in the sphere of "philosophy of technology" as well as the various implications of the multidimensional concept of Techne (the Greek root word for technology). The data and findings will next be analyzed, interpreted, and integrated. The study's achievements include addressing the philosophical foundations of design as a sub-field of technology, epistemology, and methodology, and focusing on the implications of design based on the related concepts of Techne, such as Aesthetic, Logos, Mythos, Metis, Episteme, and Poiesis, for use in future studies of the science and philosophy of design.